1997
DOI: 10.1111/j.1432-1033.1997.t01-1-00156.x
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Studies of Human Vitamin‐D Receptor by Antipeptide Antibodies, Partial Proteolytic Digestion and Ligand Binding

Abstract: We have studied conformational changes of human vitamin-D receptor by using antipeptide antibodies, partial proteolytic digestion and binding of the natural ligand calcitriol or its synthetic analogs. Before exposing either ['sS]methionine-labelled in vitro translated human vitamin-D receptor or a recombinant human vitamin-D receptor produced either in Escherichia coli or in 5 ' ' insect cells to limited proteolysis by trypsin or chymotrypsin, the proteins were treated with calcitriol or its synthetic analogs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
26
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 30 publications
4
26
0
Order By: Relevance
“…3A). Nevertheless, the work of Vaisanen et al [21] was substantiated by the R173Q-1,25D protease sensitivity assay (PSA) result, where the presence of hVDRwt-like ∼34 kDa (c1), ∼32 kDa (c2), or ∼30 kDa (c3) fragments were not observed. Alternatively, three new higher molecular weight bands were observed (a1-a3, Fig.…”
Section: Elucidation Of the Three Vdr Lbd Trypsin Cleavage Sitesmentioning
confidence: 99%
See 3 more Smart Citations
“…3A). Nevertheless, the work of Vaisanen et al [21] was substantiated by the R173Q-1,25D protease sensitivity assay (PSA) result, where the presence of hVDRwt-like ∼34 kDa (c1), ∼32 kDa (c2), or ∼30 kDa (c3) fragments were not observed. Alternatively, three new higher molecular weight bands were observed (a1-a3, Fig.…”
Section: Elucidation Of the Three Vdr Lbd Trypsin Cleavage Sitesmentioning
confidence: 99%
“…The trypsin site exposed when H12 is in the closed position (hVDR-c1, Fig. 1C) has been successfully mapped to R173 [21] (insertion loop, Fig. 1B), while the trypsin sites exposed when sterols stabilize hVDRwt-c2 and hVDRwt-c3 remain unidentified.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…The different proteolysis pattern of VDR in the presence of the natural ligand and the 20-epi compounds has been interpreted as reflecting large conformational changes of the receptor on binding of the latter class of molecules. It has been suggested that the 20-epi compounds induce an alternate conformation of the VDR-LBD, rendering the receptor more resistant to protease digestion (8,11,12,(14)(15)(16). To investigate the binding mode of the 20-epi analogs to the VDR-LBD, we determined the high resolution crystal structures of the VDR in complex with MC1288 and KH1060 ( Fig.…”
mentioning
confidence: 99%